Miniturize Flexible RFID Antenna Design using Metamaterial Structure (ELEKTRIKA- Journal of Electrical Engineering, 2019)
Radio Frequency Identification (RFID) is the application of electromagnetic fields to identify and track tags that attached on the objects. It transmits or reads the radio frequency waves in the system. However, due to rapid development of technology in telecommunication, a much more smaller and flexible device is needed. Therefore, in this paper, a new design of flexible RFID antenna using metamaterial structure has been proposed. At first, the basic rectangular microstrip patch antenna with resonant frequency of 900MHz is designed. Then, the CSRR metamaterial structure is introduced at the ground plane to reduce the size of the antenna while the polydimethylsiloxane (PDMS) material is being use as the antenna substrate for flexibility. All the simulation designs were done using CST software. The antenna performances such as resonant frequency, return loss, radiation pattern, gain and bandwidth are then be analyzed and presented. The results show good performances and can be applied for future application.